2019
DOI: 10.1001/jamanetworkopen.2018.6893
|View full text |Cite
|
Sign up to set email alerts
|

Neural Responsivity to Food Cues in Patients With Unmedicated First-Episode Psychosis

Abstract: ImportanceSchizophrenia is associated with a reduced life expectancy of 15 to 20 years owing to a high prevalence of cardiometabolic disorders. Obesity, a key risk factor for the development of cardiometabolic alterations, is more prevalent in individuals with schizophrenia. Although obesity is linked to the altered reward processing of food cues, no studies have investigated this link in schizophrenia without the confounds of antipsychotics and illness chronicity.ObjectiveTo investigate neural responsivity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
(109 reference statements)
2
8
0
Order By: Relevance
“…The regional specificity of our findings may therefore indicate that WM impairments in schizophrenia are linked to alterations in the disinhibition of synaptic transmission, arising from striatal CB1R dysfunction on GABAergic interneurons. This adds to other neurochemical evidence implicating the striatum in the pathophysiology of schizophrenia [62][63][64][65][66].…”
Section: Implications For Understanding the Neurobiology Of Working Msupporting
confidence: 56%
“…The regional specificity of our findings may therefore indicate that WM impairments in schizophrenia are linked to alterations in the disinhibition of synaptic transmission, arising from striatal CB1R dysfunction on GABAergic interneurons. This adds to other neurochemical evidence implicating the striatum in the pathophysiology of schizophrenia [62][63][64][65][66].…”
Section: Implications For Understanding the Neurobiology Of Working Msupporting
confidence: 56%
“…Another study demonstrated that FEP patients have significantly higher levels of prolactin, fasting glucose, glycosylated hemoglobin and insulin resistance compared to individuals at clinical high risk of psychosis (42). It cannot also be excluded that results of our study simply reflect the effects of environmental factors or unhealthy lifestyle characteristics that are highly prevalent in early psychosis and include nutritional deficiencies as well as low exercise activity (43)(44)(45). There are some important limitations of this study that need to be acknowledged.…”
Section: Discussionmentioning
confidence: 79%
“…The characteristics of these studies and a summary of their main findings can be found in Table 6 . Six studies used functional magnetic resonance imaging (fMRI) along with visual analog scales (VAS) and/or eating questionnaires [ 82 , 83 , 84 , 85 , 86 , 87 ] and one study used structural MRI to study brain morphology [ 88 ]. One study was conducted on AP-naïve ( n = 22) patients [ 88 ], and one was conducted on patients who were AP-naïve ( n = 9) or had been medication free for at least six weeks ( n = 20) [ 86 ] ( Section 3.2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent fMRI study, Borgan et al (2019) investigated neural responsiveness to appetitive stimuli in untreated FEP patients and HCs [ 86 ]. Comparing fMRI blood oxygen level dependent (BOLD) signaling response to appetitive stimuli between groups, the authors found that patients consistently exhibited the same regional patterns of neural activity observed in controls, indicative of normal neural responses to food cues.…”
Section: Resultsmentioning
confidence: 99%